2018
DOI: 10.1097/pap.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Clinicopathologic Features and Pathologic Diagnosis of Hepatitis E in Liver Specimens

Abstract: Infection with the hepatitis E virus (HEV) is globally seen a leading cause of hepatitis. Now increasingly recognized also in industrialized countries, hepatitis E constitutes a significant health problem worldwide. The patient's immune status determines the clinical course and histopathology of hepatitis E. In immunocompetent patients, hepatitis E usually follows an asymptomatic or subclinical course, but may also present with acute hepatitis. In contrast, immunocompromised patients may develop chronic hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
(118 reference statements)
0
10
0
Order By: Relevance
“…In humans, portal inflammation and interface hepatitis are observed in acute HEV patients [43,44]. However, fibrosis is increased in patients with chronic HEV infection [44,45]. The histopathological findings in our study indicate that mild inflammation and fibrosis are reproducible in the liver tissues of rabbits infected with swine HEV or rabbit HEV.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In humans, portal inflammation and interface hepatitis are observed in acute HEV patients [43,44]. However, fibrosis is increased in patients with chronic HEV infection [44,45]. The histopathological findings in our study indicate that mild inflammation and fibrosis are reproducible in the liver tissues of rabbits infected with swine HEV or rabbit HEV.…”
Section: Discussionmentioning
confidence: 50%
“…A histopathological study of HEV infection has also been conducted in gerbils, which showed lymphocyte and eosinophil infiltration and histiocytic hepatitis [42]. In humans, portal inflammation and interface hepatitis are observed in acute HEV patients [43,44]. However, fibrosis is increased in patients with chronic HEV infection [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Lessons from the TORCH (Toxoplasma, Others, Rubella virus, Cytomegalovirus, and Herpes simplex virus) infections have revealed that viral replication at the maternal-fetal interface is associated with tissue damage and adverse pregnancy outcome 15 , 16 . Furthermore, apoptotic and necrotic features were previously reported in liver biopsies from HEV infected patients 17 , 18 . Accordingly, we assessed whether HEV infection impairs the morphology of the maternal-fetal interface.…”
Section: Resultsmentioning
confidence: 63%
“…Mortality rates are higher among infected people presenting previous liver disease, immunocompromised patients, and pregnant women, as they present higher chances of renal failure leading to death 33,41,42 .…”
Section: Fernandes Et Al (2019)mentioning
confidence: 99%
“…Detection methods for HEV include serological (specific IgG), histopathological, and molecular (RT-PCR) techniques 41 . Commercially, there are no specific prophylatic measures available on the market, although Chinese researchers have developed the HEV p239 vaccine from the HEV1 genotype 51 .…”
Section: Fernandes Et Al (2019)mentioning
confidence: 99%